Using nominal group technique to develop COMBI related health contents of a mobile application - Mahamad Zakaria, Muhammad Luqman; Hassan, Mohd Rohaizat; Dapari, Rahmat; Abdul Halim, Ahmad Farid Nazmi; Hod, Rozita; Sharif, Khaironi Yatim; Mohd Ali, Noor Khalili; Jamhari, Mohd Nazrin; Syed Abdul Rahim, Syed Sharizman; Md Hanif, Shahrul Azhar; Mohd Radi, Mohd Firdaus; Ahmad Zamzuri, Mohd ‘ammar Ihsan; et al. (Universiti Kebangsaan Malaysia, 2024)
Introduction: The Communication for Behavioral Impact (COMBI) program functions as a platform for developing effective ways to prevent and control outbreaks in community settings that are technically sound and culturally acceptable, relevant and feasible for communities to execute. This research aimed to systematically develop the health content for the mobile application using the nominal group technique (NGT) to improve the implementation of COMBI in preventing and controlling dengue in Malaysia. Methodology: We assembled a group of individuals focusing on implementing the COMBI program and developing a mobile application. Using the NGT, a proven and structured method for conducting group meetings to reach a consensus, we agreed on the crucial contents to prioritise for developing a mobile application as the new approach to delivering the COMBI program. The panel met once via an online platform in November 2022, and the meeting lasted for two and a half hours. Results: 14 participants participated in the expert panel. During the sharing ideas activity, the panel generated 22 items. The response rate for voting was 100%. After determining the acceptance of each item, the panel retained 20 items from the original list to establish the rank order. Only one round was needed for the panel to reach a consensus to accept all the final 20 items (distributed into 11 categories) as the content for the mobile app. The selected components agreed upon by the expert panel encompassing information on COMBI, essential facts about dengue including the pathogen, the vector (characteristics of Aedes mosquito and its potential breeding sites), and the symptoms and signs, information on preventive methods including search and destroy breeding sites, application of larvicide, and methods to prevent mosquito bites, dengue situation (daily cases and outbreak report), actions during dengue outbreak, law enforcement in dengue control, update on COMBI activities, reminder alert program for search and destroy activity, dengue monitoring for dengue patient, problem reporting system, as well as Uniform Resource Locator related to dengue. These can support communities by disseminating key messages regarding dengue and equipping them with enough motivation and skills to prevent dengue transmission at the community level. Conclusion This is the first known consensus study to identify engaging mobile app content to improve the COMBI program's delivery and implementation using the NGT. We recommend the technique as an effective tool for designing interventions against communicable diseases.